Rest Before Slaughtering Alleviates Transportation Stress and Improves Meat Quality in Broiler Chickens - Tamzil , M.H.; Indarsih, B.; Jaya, I.N.S. (International Journal of Poultry Science, 2019)
Background and Objectives: Transportation of broilers generally induces stress to the birds and may lead to decrease meat quality. The study aimed to determine the effects of resting time given to the broilers after being transported prior to slaughtering on meat quality. Materials and Methods: A Completely Randomized Design was laid out using 60 female broiler chickens, aged 33 days. The broilers were divided into three groups, in which every group was given different treatments. Each group consisted of 20 female chickens as replicates. Group I (control) was not transported. Group II was transported for 3 h and after that immediately slaughtered. Group III was transported for 3 h and then slaughtered after being rested for 12 h. Shortly before and after the broilers were transported, their rectal temperature was measured and blood was taken for hematology test. Variables observed were body temperature, erythrocyte total number, hemoglobin levels, hematocrit values, total number of leukocytes, leukocyte differentiation, H/L ratio, mortality rate and meat quality. Data obtained were analyzed using Variant Analysis and LSMEAN. Results: Three hour-long transportation increased the rectal temperature, erythrocyte level, leukocyte level, heterophile percentage, H/L ratio, mortality rate and meat pH and decreased lymphocyte percentage, water holding capacity and cooking loss (p<0.01). A 12 h resting time after transportation, however, reduced the adverse effect of transportation stress on meat quality. Conclusion: The lower quality of meat owing to transportation stress can be alleviated by giving the birds rest for 12 h after transportation and prior to slaughtering.